Chemical Profile and Biological Activities of Essential Oil from Artemisia vulgaris L. Cultivated in Brazil - Sonia Malik; Ludmilla Santos Silva de Mesquita; Carolina Rocha Silva; José Wilson Carvalho de Mesquita; Emmeline de Sá Rocha; Jayakumar Bose; Rambod Abiri; Patricia de Maria Silva Figueiredo; Livio M. Costa-Júnior (Pharmaceuticals, 2019)
Essential oil from the leaves of Artemisia vulgaris L. (Compositae) cultivated in Brazil was investigated for its chemical composition and biological activities including antibacterial, antifungal, and anthelmintic. The constituents of essential oils isolated by hydro-distillation were examined by GC-MS and a total of 18 components were identified. The essential oil was dominated by oxygenated sesquiterpenes (44.4%), sesquiterpene hydrocarbons (33.3%), and oxygenated monoterpenes (16.6%). Caryophyllene (37.45%), germacrene D (16.17%), and humulene (13.66%) were the major components. The essential oils from A. vulgaris showed bactericidal and fungicidal properties against Staphylococcus aureus and Candida albicans, respectively. Anthelmintic activity against Haemonchus contortus was absent in this essential oil. Altogether above results indicate that essential oils from A. vulgaris can be used for various medicinal purposes.